2023
DOI: 10.1007/s00792-023-01313-3
|View full text |Cite
|
Sign up to set email alerts
|

Production of poly (3-hydroxybutyrate) and extracellular polymeric substances from glycerol by the acidophile Acidiphilium cryptum

Ernesto González,
Camila Zuleta,
Guiselle Zamora
et al.

Abstract: Acidiphilium cryptum is an acidophilic, heterotrophic, and metallotolerant bacteria able to use dissolved oxygen or Fe(III) as an electron sink. The ability of this extremophile to accumulate poly(3-hydroxybutyrate) (PHB) and secrete extracellular polymeric substances (EPS) has also been reported. Hence, the aim of this work is to characterize the production of PHB and EPS by the wild strain DSM2389 using glycerol in shaken flasks and bioreactor. Results showed that maximum PHB accumulation (37-42% w/w) was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Several strains of Acidiphilium cryptum can accumulate P3HB (Xu et al, 2013;González et al, 2023) while EPS production has also been reported for Acidiphilium sp. (Tapia et al, 2009(Tapia et al, , 2011González et al, 2023). The section below addresses how these aspects may be involved in biotechnological applications of these microorganisms.…”
Section: Fementioning
confidence: 83%
See 3 more Smart Citations
“…Several strains of Acidiphilium cryptum can accumulate P3HB (Xu et al, 2013;González et al, 2023) while EPS production has also been reported for Acidiphilium sp. (Tapia et al, 2009(Tapia et al, , 2011González et al, 2023). The section below addresses how these aspects may be involved in biotechnological applications of these microorganisms.…”
Section: Fementioning
confidence: 83%
“…PHAs are biopolyesters accumulated by numerous microorganisms as storage compounds, being poly (3-hydroxybutyrate) (P3HB) the most common type of PHA (Palmeiro-Sánchez et al, 2022). Several strains of Acidiphilium cryptum can accumulate P3HB (Xu et al, 2013;González et al, 2023) while EPS production has also been reported for Acidiphilium sp. (Tapia et al, 2009(Tapia et al, , 2011González et al, 2023).…”
Section: Fementioning
confidence: 99%
See 2 more Smart Citations